THE INFLUENCE OF PERCEPTION OF EASE OF USE, PERCEPTION BENEFITS, SECURITY PERCEPTION AND RISK PERCEPTION ON INTEREST IN USING SEABANK DIGITAL BANK - Dedi Supoyo; Mohd Heikal; Sapna Biby; Nurainun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to analyze the influence of Perception of Ease of Use, Perception of Benefits, Perception of Security, and Perception of Risk on Interest in Using Seabank Digital Bank in Medan City. The type of research used was quantitative with purposive sampling techniques, involving 125 respondents obtained through an online questionnaire. Primary data is collected through Google Forms, while secondary data comes from journals and internet media. The analysis techniques used include descriptive analysis, multiple linear regression, classical assumption test, validity test with Confirmatory Factor Analysis (CFA), and reliability using Cronbach Alpha. Hypothesis testing and determination coefficient were carried out using the SPSS version 26.0 program. The results of the study show that partially, the Perception of Ease of Use, Perception of Benefits, Perception of Security, and Risk Perception have a significant influence on the Interest in Using Seabank Digital Bank. The Ease of Use Perception variable is the most dominant in influencing user interest. The Adjusted R Square value of 0.460 showed that 46.0% of the variation in interest in use could be explained by the independent variable studied, while the remaining 54.0% was explained by other variables that were not included in this study.